The new taxonomy of educational objectives - Marzano, Robert J.; Kendall, John S. (Thousand Oaks, CA : Corwin Press, 2007)
Provides reference information and practical applications for educators on the nature of knowledge and cognition, covering research in three areas of knowledge and six levels of processing.
The need for a revision of Bloom's taxonomy -- The knowledge domains -- The three systems of thinking -- The new taxonomy and the three knowledge domains -- The new taxonomy as a framework for objectives, assessments, and state standards -- The new taxonomy as a framework for curriculum and thinking skills.
Includes bibliographical references (p. 169-181) and index.
Professional
Keywords: Education -- Aims and objectives; Education -- Aims and objectives